Optimization of Gelling Agents and Emulsifiers in Emulgel Bases, and Physical Evaluation of Emulgel containing Sepabang (Melastoma malabathricum L.) Leaves Extract - Nur Mita; Mirhansyah Ardana; Muhammad Arifuddin; Noor Linda Febrianie; Sofa Farida (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Sepabang (Melastoma malabathricumshot L.) leaf contains a group of phenolic compounds and has a very strong antioxidant activity so it is potentially to be developed in the form of pharmaceutical preparations. The purpose of this research is to optimize and formulate an emulgel containing Sepabang leaf extract that physically stable. Emulgel preparations are formulated using carbopol and hydroxyprophylmethylcellulose as gelling agents and Tween 60 – Span 60 and combination of triethanolamine and stearic acid as emulsifiers, with a concentration of methanol extract of Sepabang leaves of 0.25%. Physical characteristics of emulgel preparations include pH value, viscosity determination, and spreadability test evaluated at room temperature for 4 weeks. The physical stability test is done by the Freeze Thaw method for 6 cycles, of which 1 cycle consists of 48 hours at 4°C and 48 hours at 40°C. The results showed that the Sepabang emulgel that meet physical characteristic and stability parameters are F1 with HPMC as gelling agents and Tween 60-Span 60 3% as emulsifiers.